Clinicopathologic and survival analyses of synchronous primary endometrial and epithelial ovarian cancers. Issue 11 (14th September 2015) - Sozen, Hamdullah; Vatansever, Dogan; Iyibozkurt, Ahmet Cem; Topuz, Samet; Ozsurmeli, Mehmet; Salihoglu, Yavuz; Guzelbey, Burcu; Berkman, Sinan
Abstract: Aim: The aim of the study was to describe clinicopathologic characteristics, survival outcomes and the factors associated with recurrence in patients diagnosed with synchronous primary endometrial and epithelial ovarian cancers. Material and Methods: In this retrospective study, 50 patients who were diagnosed with synchronous primary endometrial and epithelial ovarian cancers and underwent surgery between 1998 and 2010 were reviewed. Results: In our study, the median age at the time of diagnosis was 53 years (range 28–79). The most common presenting symptom was abnormal uterine bleeding with a ratio of 36%. Fifty‐four percent of the patients had endometrioid type endometrial cancer and endometrioid type ovarian cancer. All patients were surgically staged and the majority of the patients were in stage I for both endometrial cancer (58%) and ovarian cancer (60%). Nearly one‐third (32%) of the patients had a recurrence during the follow‐up period and by Cox regression analysis the level of cancer antigen 125 ( P  = 0.023) at diagnosis, serous or clear‐cell histopathologic type ovarian cancer ( P  = 0.029) and stage of endometrial cancer above I ( P  = 0.048) were found to be independent risk factors associated with development of recurrence. Patients with endometrioid type endometrium histology and endometrioid type ovarian histology had favorable prognosis with 120.00 months mean disease‐free survival and 92% disease‐free survival rate at 36 months. Conclusion: In our cohort, we found that endometrioid/endometrioid type synchronous primary endometrial and ovarian cancer had different clinical histopathologic characteristics and favorable prognosis compared to the other histologic types of these cancers. Histopathologic type of the ovarian cancer component, stage of endometrial cancer and level of cancer antigen 125 at diagnosis were observed to have a great influence on the development of recurrence and survival of synchronous primary carcinomas of the endometrium and ovary.